The predictive value of NLR,RDW and C-reactive protein for acute pancreatitis with severe acute kidney injury - ZHANG Zhi-qin; WEI Mao-bi; WANG Bai-ying; ZHANG Lian; ZHA Dong-qing; WU Xiao-yan (Linchuang shenzangbing zazhi)
Objective To investigate the predictive value of neutrophil/lymphocyte ratio(NLR),red blood cell distribution(RDW)and C-reactive protein for acute pancreatitis with severe renal injury.Methods In this retrospective study,we collected 71 cases of patients with acute pancreatitis with acute kidney injury(AP&AKI)from January 2014 to July 2019 admitted in Department of Liver-Gallbladder-Pancreas,Zhongnan Hospital of Wuhan University.In the AP&AKI group,there were 23 cases of AKI phase I,27 cases of AKI phase II,21 cases of AKI phase III;and there were 100 cases in the AP group.The diagnostic criteria and phasing of acute pancreatitis complied with Chinese Guidelines for Diagnosis and Treatment of Acute Pancreatitis,and the diagnostic criteria and phasing of acute kidney injury with the KIDIGO guideline. The basic data and biochemical test results in the two groups were collected and analyzed for their early prediction value for acute pancreatitis with severe acute kidney injury.Results NLR,CRP,RDW14 % in the AP&AKI phase Ⅲ group were significantly higher than those in the AP group,and partly suggested that the degree of inflammation and AKI kidney damage indices were higher than in the AP with mid and moderate AKI groups.Conclusions NLR,CRP and RDW14% exhibit significant differences in acute pancreatitis with severe acute kidney injury,and have certain predictive value,but not as high as the combination of the three.